2022
DOI: 10.3389/fmicb.2022.839524
|View full text |Cite
|
Sign up to set email alerts
|

Pangenome Analysis of the Soilborne Fungal Phytopathogen Rhizoctonia solani and Development of a Comprehensive Web Resource: RsolaniDB

Abstract: Rhizoctonia solani is a collective group of genetically and pathologically diverse basidiomycetous fungi that damage economically important crops. Its isolates are classified into 13 Anastomosis Groups (AGs) and subgroups having distinctive morphology and host ranges. The genetic factors driving the unique features of R. solani pathology are not well characterized due to the limited availability of its annotated genomes. Therefore, we performed genome sequencing, assembly, annotation and functional analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…This was first studied within yeasts such as Saccharomyces cerevisiae (63% of orthologs in the core genome of >1k genomes; Peter et al 2018 ), Cryptococcus neoformans , and Candida albicans (80–90% orthogroups form the core genome; McCarthy and Fitzpatrick 2019 ). More recent work with multicellular fungi has found a similar level of genomic conservation ( Zymoseptoria tritici , Badet et al 2020 ; Rhizoctonia solani , Kaushik et al 2020 ; and Neonectria neomacrospora , Nielsen et al 2021 ). Studies that consider a wider diversity of genomes have also found maintenance of a high percentage of gene orthogroups ( Okagaki et al 2016 ; Wang et al 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…This was first studied within yeasts such as Saccharomyces cerevisiae (63% of orthologs in the core genome of >1k genomes; Peter et al 2018 ), Cryptococcus neoformans , and Candida albicans (80–90% orthogroups form the core genome; McCarthy and Fitzpatrick 2019 ). More recent work with multicellular fungi has found a similar level of genomic conservation ( Zymoseptoria tritici , Badet et al 2020 ; Rhizoctonia solani , Kaushik et al 2020 ; and Neonectria neomacrospora , Nielsen et al 2021 ). Studies that consider a wider diversity of genomes have also found maintenance of a high percentage of gene orthogroups ( Okagaki et al 2016 ; Wang et al 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…Gene PAV plays an important role in fungal pan-genome evolution [2][3][4][5]. To improve our understanding of these events, we designed a robust pipeline to identify orthogroups experiencing PAV in M. oryzae.…”
Section: Discussionmentioning
confidence: 99%
“…While bacteria typically gain and lose genes in the form of large horizontal gene transfer events [1], the accessory portion of fungal pan-genomes, which is defined in contrast to the conserved set of genes found in all members of a species, are typically shaped by small gene duplication and deletion events, which contribute to gene presence-absence variation (PAV) [2]. Previous fungal pan-genome studies have focused on the roles and functions of core and accessory genes [2][3][4][5], but our knowledge of which genomic and epigenomic features shape fungal pangenomes remains limited. Some studies have highlighted an association of accessory genes with subterminal chromosomal regions and transposable elements (TEs) [2,3], but it is uncertain whether these associations are strong enough to be predictive of gene PAV.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively few studies have examined the relationship between R. solani AG3 and other economically important crops, including tobacco. Recently, the draft genome sequence of R. solani AG3 became publicly available and was refined, thereby providing thorough knowledge of the architecture, variation, and evolution of the pathogen and enabling more in-depth genetic study of R. solani AG3 ( Shu et al., 2021 ; Kaushik et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%